Impact of inhibitors associated with lignocellulosic hydrolysates on recombinant cellulolytic enzymes - Mhlongo, Sizwe Innocent (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.